Mixing performance in continuous oscillatory baffled reactors. (29th June 2020) - Avila, M.; Fletcher, D.F.; Poux, M.; Xuereb, C.; Aubin, J.
Graphical abstract: Highlights: Mixing quality can be improved in COBRs by changing the position of the feed source. Poor mixing occurs when the source is located at the tube centreline. Better mixing performance is achieved when the source is closer to the reactor wall. Mixing performance increases with an increase in the velocity ratio. Higher oscillation frequencies lead to improved mixing quality. Abstract: In the current literature, there is limited information on the influence of operating parameters on spatial mixing quality and how a secondary feed should be introduced into continuous oscillatory baffled reactors (COBR) to achieve good mixing quality. This work explores for the first time the impact of the position of a secondary feed (passive non-reactive tracer) on spatial mixing performance in a COBR using transient laminar CFD simulations. Three theoretical feed positions are studied covering a range of net flow and oscillatory Reynolds numbers ( Re net = 6 - 27 / Re o = 24 - 96 ), the range being chosen to ensure that the flow field remains two-dimensional in all cases. Macromixing is evaluated by analysing the spatial uniformity of the tracer with the areal distribution method developed by Alberini et al. (2014a). Introduction of the secondary stream at the reactor wall or upstream of the edge of the first baffle greatly improves mixing quality due to the recirculation eddies, which assist radial mixing. However, introduction of the secondary feed at the centreline results in high axial dispersion with limited radial mixing. With an adequate introduction position, mixing quality typically increases with an increment in the velocity ratio. Nevertheless, if the net flow is too low, mixing performance decreases because the secondary stream is pushed upstream of the baffles, where it does not benefit from flow recirculation.